THE INFLUENCE OF POLITICAL COMMUNICATION ON PUBLIC POLITICAL PARTICIPATION IN THE 2024 CONVENIENT REGIONAL HEAD ELECTIONS (PILKADA) IN SOUTH KALIMANTAN - M. Agus Humaidi (Jurnal Ekonomi, 2022)
Communication plays an important role in achieving political goals and as a communication tool for political campaigns. One of the goals of political communication is to urge political participation. Community political participation in all stages of the election is a sign of the success and quality of holding elections. This research aims to analyze the influence of political communication on people's political participation in the 2024 Pilkada in South Kalimantan. The methodology used in this research is through literature research and analysis using content analysis methods. The results of the research prove that the 2024 simultaneous local elections in South Kalimantan show the level of public political participation that will be influenced by political communication by political actors. So the hypothesis in this research is that political communication affects people's political participation in the 2024 simultaneous Regional Head Elections (Pilkada) in South Kalimantan.